2013
DOI: 10.1158/2159-8290.cd-12-0592
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Interrogation of 3q26 Identifies TLOC1 and SKIL as Cancer Drivers

Abstract: 3q26 is frequently amplified in several cancer types with a common amplified region containing 20 genes. To identify cancer driver genes in this region, we interrogated the function of each of these genes by loss- and gain-of-function genetic screens. Specifically, we found that TLOC1 (SEC62) was selectively required for the proliferation of cell lines with 3q26 amplification. Increased TLOC1 expression induced anchorage independent growth and a second 3q26 gene, SKIL (SNON), facilitated cell invasion in immor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 49 publications
5
62
0
4
Order By: Relevance
“…The same study also found that SMAD4 knockdown increased the invasiveness of human mammary epithelial cells, while SKIL overexpression had no effect on cell growth, in agreement with our findings [28]. Another recent study has proposed that SKIL can interact with and promote the activity of estrogen receptor α in the nuclei of breast carcinoma cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The same study also found that SMAD4 knockdown increased the invasiveness of human mammary epithelial cells, while SKIL overexpression had no effect on cell growth, in agreement with our findings [28]. Another recent study has proposed that SKIL can interact with and promote the activity of estrogen receptor α in the nuclei of breast carcinoma cells.…”
Section: Discussionsupporting
confidence: 91%
“…Overexpression of either SKI or SKIL in chicken embryo fibroblasts is sufficient to induce oncogenic transformation [26], and SKIL expression is elevated in many human cancers, including cancers of the skin, breast, colon and blood [27]. The 3q26 locus is amplified in several cancer types, and SKIL (along with TLOC1 ) has been highlighted as the most potent oncogene in this region [28]. Both SKI and SKIL contain an 80 aa SAND-like domain that can bind with the MH2 domain of SMAD4 [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one coding gene, SEC62 (also named TLOC1), showed two circular RNAs that differed in terms of number of the exons involved. These two circRNAs were located in the chromosome region 3q26.2, that it is interestingly frequent amplified in several cancers [21]. The longest in terms of nucleotides (11414 nts) was the hsa-circ-0001358 (alias hsa-circ-001803), while the second was hsa-circ-0122662, 8920 nts long.…”
Section: Resultsmentioning
confidence: 99%
“…A possible exception may be the 3q26 amplicon. Indeed, the 3q26 locus is frequently amplified in various types of cancer (ovarian, breast, and non-small cell lung cancers) and is correlated with poor prognosis and an invasive phenotype (41,42). PLD1 was identified as a resident gene in the minimal common amplified region of 3q26 (42).…”
Section: Genomic Alternation Of Pld1 Gene In Cancermentioning
confidence: 99%